Transitional Delays and Social Vulnerability in Contemporary Population Dynamic. Argentina, 2001-2013 - González, Leandro M. (2015)
This article explores the demographic dynamics since the beginning of the century in Argentina to consider the social consequences produced by the 2001-2002 economic crisis. The notion of transitional lag (persistence of high levels of fertility and mortality with a youthful age structure) is used to contrast the different population profiles with different positions in social structure, from the perspective of sociodemographic vulnerability. Main demographic indicators for 2001 and 2010 census and for the last published vital statistics (2013) are calculated using a population projection. This is done for Argentina Republic as a whole and one province for each region. The results show a positive evolution of demographic indicators in the country although with persistence of the structural differences between regions. The Argentine Northeast is the region with the largest transitional lag, while the remaining regions are concentrated around national values and the Capital has a much more advanced profile. Life expectancy at birth has increased in all jurisdictions, with more intensity in males than in females, and faster in the period 2001-10. Total fertility recorded a mild decline, while the adolescent fertility is reluctant to decline. Overall Argentine population has experienced a breakthrough in the process of demographic transition that coexists with situations of transitional lag: regional heterogeneity, increasing adolescent fertility, and transient decreases in general and infant mortality.